Policy implications of trade and currency zones : a symposium sponsored by the Federal Reserve Bank of Kansas City - Federal Reserve Bank of Kansas City. (Kansas City, Mo. : Federal Reserve Bank of Kansas City, 1991)
Summarizes the symposium papers and discussions supporting the move to a trade and currency zone in Europe, although some expressed doubt about the benefits of trade and currency zones in other parts of the world.
Includes bibliographical references.
opc 06/09/2016
Loans
Keywords: International trade; Free ports and zones; Banks and banking-International; International economic relations; Foreign exchange